Addressing Revenge Porn Through Islamic Ethics and Cyber Ethics: An Analysis from A Fiqh Sunnah Perspective - Raihana, Siti Nazla; Muhamad Arifin; Vivi Aryati (al-Afkar, Journal For Islamic Studies, 2025)
This study delves into the phenomenon of revenge porn in Indonesia, examining it through the lenses of Islamic ethics, cyber ethics, and Fiqh Sunnah. In 2023, revenge porn and sextortion constituted a troubling 40% of gender-based violence against women in the country. Employing a mixed-method approach, which combines library research with interviews of Indonesian victims aged 18 to 36, the findings reveal a stark contradiction with Islamic ethics. Revenge porn violates principles of privacy, decency, trust, and mutual consent, and it neglects reputation protection, endangering individuals. Notably, the study sheds light on the absence of justice in addressing revenge porn, a significant deviation from Islamic principles of justice and fairness. Additionally, the research underscores how revenge porn contradicts cyber ethics, where perpetrators disregard online responsibility, privacy protection, and respectful online behavior. The study advocates for comprehensive measures to uphold ethical standards, providing support for victims, and fostering a secure digital environment that respects individual dignity and rights. A particular emphasis is placed on the significance of cyber ethics in combating revenge porn and addressing the perpetrators' failure to adhere to responsible online behavior.